A diszpozicionális hála és a mentális egészség kapcsolata várandós nők körében - Andrea FERENCZI; Zsuzsanna KÖVI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2022)
The Relationship between Gratitude and Mental Health among Pregnant Women. BACKGROUND – Becoming a mother, that is the forty weeks of pregnancy, is a highlighted stage of life for a woman. It is a defining period for both the mother and her child, who is to be born. Furthermore, gestation can be under-stood as a normative crisis as well, during which numerous psychological prob-lems may evolve. Therefore, the preservation of mental health and support pro-vided for women are especially important in prenatal care. GOALS – The purpose of this study is to examine the role of gratitude, appreci-ation, subjective well-being, and social support – as momentous constructs of health psychology – in assisting mental health in the lives of pregnant women and to explore the relations between these variables. METHODS – 79 pregnant women participated in our online, qualitative inves-tigation; 36 of them had been writing gratitude diaries for 4 weeks. We com-pared the questionnaires’ results (filled out both before and after the interven-tion) of the experimental group (n = 36) with the results of the control group (n = 43) similarly filled out on two different occasions. The following instruments were used in our study: Gratitude, Resentment, and Appreciation Test; Appre-ciation Scale; Subjective Well-Being Questionnaire; MOS Social Support Sur-vey. RESULTS – Higher appreciation and dispositional gratitude correlates with a higher sense of subjective well-being and a better perception of social support. In the experimental group, writing a gratitude diary was followed by a signifi-cant positive change in all questionnaires: the scores for gratitude, appreciation, subjective well-being, and social support increased. CONCLUSIONS – Dispositional gratitude that can be improved by such a simple intervention as writing a gratitude diary is a useful means of supporting the mental health of pregnant women and thereby of preserving and promoting their psychological and physical well-being. Besides medical healthcare, ex-pectant women are in particular need of professional mental support, wherefore it is important not only to maintain their physical health but also to introduce new methods that assist mentally the well-being of pregnant persons.